Avaliability model for reconfigurable network - Liang ZHAO; Xiao-hui ZHANG; Yu WANG (Tongxin xuebao)
For network fault recovery mechanisms can have a significant impact on network performance reconfigurable actual situation theoretically analyze the running reconfigurable networks, a reconfigurable network availability model is proposed. In this model, quantitative description of the node service capabilities and network services capabilities, based on reconfigurable network by introducing state transition theory, finite-state Markov chain theoretical analysis. To verify the validity of the availability of the model by simulation, simulation results show that the theoretical model calculations and simulation results fit better, can be used to describe the specific performance reconfigurable networks available.